PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), EARNING PER SHARE (EPS), DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA SAHAM INDEKS LQ45 YANG TERDAFTAR PADA BURSA EFEKINDONESIA - Wira Yudha Ervanto Putra, 12.05.51.0109; Sudarsi, Sri (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Â CR, DER, EPS and ROA on Stock Prices in LQ45 company is go public in Indonesian Stock Exchange. The research wasconducted again because that empirical evidence were linked with fundamental factors with stock prices still showed the different results that need further research to prove how the influence of fundamental factor on stock prices especially the LQ45 sector in Indonesian Stock Exchange. This study was taken because there are still differences between the research study with each other.This research was conducted using secondary data. Population in this research was LQ45 company obtained from share which was listed and âgo publicâ in Indonesian Stock Exchage period 2013-2015. Sampling technique used waspurposive sampling. There is 68 companies that can be analysed. This study is analyzed by using multiple regression.The multiple regression shows that CR have negative and significant impact on stock prices , DER has positive andnot significant effect on stock prices, EPS and ROAhave positive and significant impact on stock prices. Adjusted R Square is 0.850 this means 85% of the dependent variable can be explained by the independent variable , while the remaining 25% is explained by other causes outside the modelÂ Keywords: Stock Price, Current Ratio,Debt to Equity Ratio, Earning Per Share and Return On Assets.